The Analytic Cauchy Problem with Singular Data - Lamport, Leslie (Brandeis University, 1972)
I left Marlboro College and went back to Brandeis in 1969 to complete my Ph.D. At that time, I intended to study and write a thesis in mathematical physics. However, I wound up doing a thesis in pure mathematics, on analytic partial differential equations. I learned nothing about analytic partial differential equations except what was needed for my thesis research, and I have never looked at them since then. The thesis itself was a small, solid piece of very classical math. Had Cauchy arisen from the grave to read it, he would have found nothing unfamiliar in the mathematics.